PERBANDINGAN MODEL DISCOVERY LEARNING DENGAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SMA - Mutmainah; Mikrayanti (Universitas Teknokrat Indonesia, 2026)
The Discovery Learning and Problem-Based Learning models each offer unique characteristics at every stage of learning, demonstrating their respective strengths through the process of solving mathematical problems involving exponential concepts. Research comparing these two models remains limited in scope, with a focus on providing an empirical contribution to students’ mathematical problem-solving abilities. This study aims to examine differences in the improvement of mathematical problem-solving skills between students learning through the Discovery Learning model and those learning through the Problem-Based Learning model. The study employs a quasi-experimental approach with a Nonequivalent Comparison Group design. The study population consists of all 75 tenth-grade high school students. Cluster random sampling was used to select two classes as the sample: Class XA and Class XB, each consisting of 25 students. The research instrument was a mathematics problem-solving ability test designed based on the indicators of understanding the problem, planning the solution, implementing strategies, and evaluating the results. Data analysis was conducted using descriptive and inferential statistics, specifically an ANOVA test. Prior to the inferential test, prerequisite tests—namely, normality and homogeneity tests—were performed to ensure the data’s suitability. The results of the study indicate that there was no significant difference in the improvement of mathematical problem-solving skills between the Discovery Learning class and the Problem-Based Learning class. These findings suggest that both models are equally effective in improving students’ mathematical problem-solving skills in the area of exponents.